The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/2317-1545v42241633
|View full text |Cite
|
Sign up to set email alerts
|

Seed quality analysis of Senna siamea Lam. using image analysis techniques

Abstract: The inclusion of image analysis techniques for the accurate and rapid assessment of the quality of forest seeds is highly desirable. The use of digital radiographic images of seeds and the analysis of seedling images, still little used in determining the quality of forest seeds, are among the available imaging techniques. This study aimed to assess the feasibility of using the analysis of images of seeds and seedlings in the assessment of the physical and physiological quality of Senna siamea seeds. Radiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Moreover, the manual or visual counting of seeds is tiring, repetitive, inefficient and increases the chances of human error, which can be overcome with the use of image processing techniques (Mussadiq et al, 2015;Acosta et al, 2017;Deng et al, 2021). ImageJ® is a free access software with several applications in image analysis in agrarian and biological sciences (Noronha et al, 2019;Freitag et al, 2020;Medeiros et al, 2020;Silva et al, 2020;Oliveira et al, 2021;Ribeiro et al, 2021). Among them, the possibility of counting elements in an image for different purposes (Passoni et al, 2014;Gautier and Ginsberg, 2021;Tsuzuki et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the manual or visual counting of seeds is tiring, repetitive, inefficient and increases the chances of human error, which can be overcome with the use of image processing techniques (Mussadiq et al, 2015;Acosta et al, 2017;Deng et al, 2021). ImageJ® is a free access software with several applications in image analysis in agrarian and biological sciences (Noronha et al, 2019;Freitag et al, 2020;Medeiros et al, 2020;Silva et al, 2020;Oliveira et al, 2021;Ribeiro et al, 2021). Among them, the possibility of counting elements in an image for different purposes (Passoni et al, 2014;Gautier and Ginsberg, 2021;Tsuzuki et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis was performed through images, with the seedlings arranged on a flat surface with a blue background, next to a ruler graduated in cm, with the image captured using a camera with 300 dpi resolution and in jpeg format. Subsequently, the images were processed using ImageJ® software, and adjustments were made to the contour of the seedlings, making it possible to obtain the length of the parts (root, shoot and seedling), with the results expressed in cm (Silva et al, 2020).…”
Section: Variables Analyzedmentioning
confidence: 99%
“…This may compromise the accuracy of results and visualization of seed internal morphology. In Leucaena leucocephala [31] and Senna siamea [15] seeds, tissuedensity-related parameters could be compared through radiographs, and their moisture levels ranged from 8.1% to 8.8% and from 11.5% to 12.9%, respectively. Moisture uniformity among the analyzed lots is another aspect that must be considered for standardized evaluations and safe comparisons of seed physiological quality [32].…”
Section: Implications For Seed Viabilitymentioning
confidence: 99%
“…Integrated density is calculated considering the gray values of each image pixel, differing from relative density calculations that consider seed area [13]. Recently, seed research has reported the potential of both parameters to evaluate seed lots for different species [11,[14][15][16]. However, although the results of physical parameters generated by X-ray analysis are effective in differentiating seed lots, they must be compared to physiological tests in order to accurately infer their potential relationship with seed physiological quality [13].…”
Section: Implications For Seed Viabilitymentioning
confidence: 99%
See 1 more Smart Citation